Analisis Kelayakan Usaha Rumah Potong Hewan di Kabupaten Muaro Jambi: Studi Kasus RPH Cahaya 9 - Bambang Saputro; Firmansyah Firmansyah; Fachroerrozi Hoesni (Universitas Batanghari, 2021)
This study aims to determine the business feasibility of RPH which is a case study of Cahaya 9 slaughterhouse from technical aspects and financial aspects as well as sensitivity. This research was conducted from November 5th to December 4th 2020. The object observed in this study was the Cahaya 9 Private Slaughterhouse (RPH) in Muaro Jambi Regency. The data obtained from this study are primary data and secondary data. The results of technical and technological analysis show that only 46.88% of the facilities in Cahaya 9 Slaughterhouse comply with the provisions of the Regulation of the Minister of Agriculture Number 13 / Permentas / OT.140 / 1/2010 concerning Requirements for Slaughterhouses and Meat Handling Units. ) and SNI 01-6159-1999 concerning animal slaughterhouses.Financial analysis at an interest rate of 12 % shows that Net Present Value > 1 (2,033,681,438), Net Benefit / Cost > 1 (3.10) and Internal Rate of Return > 1 (66.59). The results of this analysis indicate that the light 9 RPH business is financially feasible to continue. Financial feasibility but sensitive to changes (increase) in purchasing capital for livestock. The cost of purchasing beef cattle reaches 97.10% of the total operating costs. At an interest rate of 12 %, the cost of purchasing beef cattle will result in an NPV <1 of -8,488,856,574, Net B / C <1 of -7.78 and an IRR of negative, which results in the business being unfit.